Analysis Of The Bangkir Moving Dam As A Flood Control Measure In The Indramayu Regency Area - Farrel Arkananta Riyanto; Mashadi Putra; Kahfi Anwar Ghiffary; Nurdiyanto Nurdiyanto (Journal of World Science, 2025)
This study analyzes the capacity of the Bangkir Movable Dam as a strategic solution to control flooding downstream of the Cimanuk River in Indramayu, which often occurs due to river overflow. This quantitative study uses rainfall data over a 10-year period (2015–2024) to calculate the design flood discharge, with the Weduwen method selected as the primary reference due to its most conservative estimates. The analysis results determine the 50-year return period flood discharge (Q50) at 599.58 m³/s. Meanwhile, the total dam capacity, calculated using the Sharp-Crested Weir method, reaches 1,329.68 m³/s. The comparison shows that the existing dam capacity is significantly larger than the planned flood discharge. Thus, the Bangkir Movable Weir is considered effective and capable of controlling floods for a return period of up to 100 years, thereby reducing the risk of flooding in the Indramayu region.